The Impact of Boys' Love Series on Adolescent Sexual Orientation from Islamic Perspective - Salma Nuha Ghufron; Siti Nazla Raihana (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2023)
The surge in popularity of Boys' Love series within Indonesia's Gen Z has raised concerns for its promotion of LGBTQ+ themes. This research focuses on studying the impact of watching Boys' Love on adolescent sexual orientation. Over a two-month period, a qualitative research study centered on 19 screened respondents from South Jakarta, identified as Boys' Love viewers, aimed to understand the factors driving teenagers to engage with this content, its impact on their sexual orientation, and the corresponding Islamic perspective. The study uncovers five dominant factors motivating teenagers to watch Boys' Love series, shedding light on potential influences on the mental and moral development of adolescents. Additionally, it explores Islamic attitudes toward these influences, emphasizing both preventive and curative measures to address sexual deviations in adolescents. These findings emphasize the necessity for awareness among today's Gen Z, urging selective media consumption for leisure. This study underscores the importance of cultivating a different understanding of Islamic principles, encouraging the younger generation to equip themselves with knowledge and implement Islamic values to prevent potential negative impacts on their mental and moral well-being. Therefore, balancing current trends with cultural and religious values is important to navigate the influence of media on the younger generation.